The Ethical Function of Intertextual References to Deuteronomy in Proverbs 1–9 as a Moral Tradition - Kim, Daniel Hyung Seok (My University, 2024)
In this dissertation, I examine the ethical functions of Deuteronomic references in Prov 1–9 to observe how they are utilized in parental discourse to guide the youth toward moral formation. To analyze the ethical dimension of these intertexts, this study employs an interdisciplinary methodology that integrates MacIntyre’s meta-ethical framework and Culler’s Presupposition theory. The Deuteronomic language embedded in parental instructions is categorized into three thematic complexes: the Shema (Prov 3, 6, 7), the Way metaphor concerning “life in the land” (Prov 2:21–22), and the fear of YHWH (Prov 1:7; 2:5; 9:10). These thematic clusters are then mapped onto the meta-ethical categories of practice, narrative, and telos to further assess their moral implications in the discourse in Prov 1–9. With their active role in character formation, I conclude that they represent a Deuteronomic moral tradition that shapes and transforms the youth’s understanding of socio-ethical practice, narrative unity, the foundation, and purpose of life as the covenant people of God.